The Ayatollah Begs to Differ: The Paradox of Modern Iran by Hooman Majd (New York, Doubleday, 2008. hbk. 272 pages) (American Journal of Islam and Society, 2011)
Hooman Majd, a former writer for the Rolling Stone and movie producer,is uniquely qualified to write a book about Iran for an American audience.As he admits, “A friend once told me that that I was the only personhe knew who was both 100 percent American and 100 percent Iranian.Oxymoronic as that sounds, I knew what he meant. I was raised andeducated completely in the West, but am the grandson of a well-respectedAlameh (learned) and Ayatollah; my first language is English, but I am alsofluent in Farsi and am told that I speak it without an identifying accent.But more important, my Western outlook on life doesn’t interfere with mycomplete ease in the company of even the most radical of Iranian politicalor religious figures (and often theirs with me), and in my travels to IranI have often thought there must be a toggle switch somewhere along theelectrical system in my brain that is magically triggered to ʻEast’ whenmy plane crosses into Iranian airspace (8‒9).” Due to this toggle switch,Majd is able to highlight the very important role Persian culture plays in Iranian history and politics ‒ challenging the assumptions often madeabout Iranian clerics, politicians, and citizens ...